Clinical Characteristics of Early-Onset and Late-Onset Leigh Syndrome - Hong, Chan-Mi; Na, Ji-Hoon; Park, Soyoung; Lee, Young-Mock (Frontiers in Neurology, 2020)
Background: Leigh syndrome (LS) is the most common pediatric mitochondrial diseases caused by MRC defect. LS patients typically have onset age before 2 years old and have various clinical features. The purpose of this study was to evaluate the various characteristics between the group that were early onset and late onset patients. Methods: The medical records of this study used records between 2006 and 2017 (N = 110). Clinical characteristics, diagnostic evaluations and neuro image studying of LS were reviewed in our study. We statistically analyzed data from patients diagnosed with LS at our hospital by using subgroup analysis was performed to divide patients according to the onset age. Results: Among the patients, 89 patients (80.9%) had the onset age before 2 years old, and 21 patents (19.1%) had onset age after 2 years old. In subgroup analysis first clinical presentation age, diagnosis age and several onset symptoms in the clinical characteristics were statistically significant. Early onset age group showed delayed development and late onset age group showed motor weakness and ataxia. However, Diagnostics evaluation and MRI findings showed no significant differences. The clinical status monitored during the last visit showed statistically significant differences in the clinical severity. In the early onset age group clinical status was more severe than late onset age group. Conclusions: Although the onset of Leigh syndrome is known to be under 2 years, there are many late onset cases were existed more than expected. Early onset LS patients have poor prognosis compare with late onset LS patients. Therefore, the specific phenotype according to the age of onset should be well observed. Onset of LS is important in predicting clinical severity or prognosis, and it is necessary to provide individualized treatment or follow-up protocols for each patient.